Venezuela: retos de un país petrolero al diversificar su economía reducir su vulnerabilidad externa (2009)
Venezuela is one of the first oil-producing countries of the world, with huge reserves of conventional and extra-heavy oil and natural gas.TheVenezuelan oil legislation aimed to increase fiscal revenues since the very beginning of the oil exploitation in the country. The nationalization of the industry in 1975 added a new goal: the redistribution of wealth among Venezuelan society. But it provoked a rent seeking mentality dependent on oil, and preventing the diversification of Venezuelan economy after ninety years of activities. On the contrary, it has become more dependent than ever in the oil industry. The policies decided during the present decade have substituted the policies adopted in the 90´s, oriented to internationalize the industry and to expand the production through association with private capital. The new direction has strengthened the predominance of the State and changed the technical character of Petroleos de Venezuela SA, PDVSA (state owned firm in charge of oil activities), which has turned out in inefficiencies, low investment and fall in the oil production. The deterioration of Venezuela internal economic system has forced the increase of imports. Public expenditures are now the engine of the economy, further aiding wasteful consumption and inflation. In addition, the oil has become the column of the country´s international diplomacy, which involves high foreign commitments, plus enormous domestic subsidies than threaten the fiscal sustainability of the country at medium and long term.